Reconstruction after hemisacrectomy with a novel 3D-printed modular hemisacrum implant in sacral giant cell tumor of the bone - Lv, Zhaorui; Li, Jianmin; Yang, Zhiping; Li, Xin; Yang, Qiang; Li, Zhenfeng (Frontiers in Bioengineering and Biotechnology, 2023)
Background There are a limited but increasing number of case reports and series describing the use of 3D-printed prostheses in bone tumor surgery. Methods We describe a new approach to performing nerve-preserving hemisacrectomy in patients with sacral giant cell tumors with reconstruction using a novel 3D-printed patient-specific modular prosthesis. The series included 4 female and 2 male patients with a mean age of 34 years (range, 28-42 years). Surgical data, imaging assessments, tumor, and functional status, implant status, and complications were retrospectively analyzed in six consecutive patients. Results In all cases, the tumor was removed by sagittal hemisacrectomy and the prosthesis was successfully implanted. The mean follow-up time was 25 months (range, 15-32 months). All patients in this report achieved successful surgical outcomes and symptomatic relief without significant complications. Clinical and radiological follow-up showed good results in all cases. The mean MSTS score was 27.2 (range, 26–28). The average VAS was 1 (range, 0-2). No structural failures or deep infections were detected in this study at the time of follow-up. All patients had a good neurological function. 2 cases had superficial wound complications. Bone fusion was good with a mean fusion time of 3.5 months (range, 3-5 months). Conclusions These cases describe the successful use of custom 3D-printed prostheses for reconstruction after sagittal nerve-sparing hemisacrectomy with excellent clinical outcomes, osseointegration, and durability.